Phenotype and genotype spectra of a Chinese cohort with nephronophthisis-related ciliopathy. Issue 2 (15th December 2020) - Tang, Xiaoshan; Liu, Cuihua; Liu, Xiaorong; Chen, Jing; Fan, Xiaoyan; Liu, Jialu; Ma, Duan; Cao, Guanghai; Chen, Zhi; Xu, Daliang; Zhu, Ying; Jiang, Xiaoyun; et al.
Abstract : Background: Nephronophthisis-related ciliopathies (NPHP-RC) account for the majority of cases of monogenetically caused end-stage renal disease (ESRD) in children. Exploring the correlation between the phenotype and genotype of NPHP-RC is helpful for early diagnosis and management. We investigated the phenotype and genotype spectra of NPHP-RC in a Chinese multicentre cohort. Methods: Crosss-ectional and longitudinal data of 60 patients from 57 families with pathogenic NPHP-RC gene mutations distributed in 22 regions of China were collected into a unified, anonymous database. The mean observation time of this cohort was 3.5±3.1 years. Results: Mutations in NPHP1 and NPHP3 were the most common genetic defects. Overall, 45% of patients presented with isolated nephronophthisis (NPH), and 55% exhibited the extrarenal phenotype, which frequently involved the liver (41.7%, n=25), central nervous system (26.7%, n=16), eyes (26.7%, n=16) and skeletal system (11.7%, n=7). Accidental detection of elevated serum creatinine and non-specific symptoms caused by chronic kidney disease occurred in 65% of patients. Patients carrying NPHP1 mutations mainly presented with isolated NPH (90%, 18/20) and progressed to ESRD at a mean age of 12.9±0.5 years. The mean age of ESRD onset in the non- NPHP1 group was lower than that in the NPHP1 group (6.2±1.4 years, p<0.001), especially for patients carrying NPHP3 mutations (3.1±1.2 years), showing a heterogeneous phenotype characterised by Bardet-Biedl syndrome (12.5%, n=5), Joubert syndrome (7.5%, n=3), COACH syndrome (2.5%, n=1), Mainzer-Saldino syndrome (2.5%, n=1), short-rib thoracic dysplasia (2.5%, n=1) and unclassified symptoms (32.5%, n=13). Conclusions: The Chinese Children Genetic Kidney Disease Database registry characterised the spectrum of the phenotype and genotype of NPHP-RC in the Chinese population. NPHP1 and NPHP3 were the most common pathogenic genes. Rapid progression to ESRD and liver involvement were noted in patients with NPHP3 mutations.